2012
DOI: 10.1117/12.913559
|View full text |Cite
|
Sign up to set email alerts
|

Signal-known exactly detection performance in tomosynthesis: does volume visualization help human observers?

Abstract: Tomosynthesis produces three-dimensional images of an object, with non-isotropic resolution. Tomosynthesis images are typically read by human observers in a stack viewing mode, displaying planes through the tomosynthesis volume. The purpose of this study was to investigate whether human performance in a signal-known exactly (SKE) detection task improves when the entire tomosynthesis volume is available to the observer, compared to displaying a single plane through the signal center. The goal of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The actual appearance of the signal in the reconstructed tomosynthesis image depends on its location relative to the x-ray source path. This is expected and was the reason for matching signal and ROI location in the first place, because differences due to mismatched geometry are noticeable by human observers, in particular, if the 3D tomosynthesis volume is displayed (Reiser and Nishikawa 2012). To make this more clear, one can inspect a tomosynthesis plane perpendicular to the detector and observe that objects are blurred and slightly tilted toward the center of the xray source path.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The actual appearance of the signal in the reconstructed tomosynthesis image depends on its location relative to the x-ray source path. This is expected and was the reason for matching signal and ROI location in the first place, because differences due to mismatched geometry are noticeable by human observers, in particular, if the 3D tomosynthesis volume is displayed (Reiser and Nishikawa 2012). To make this more clear, one can inspect a tomosynthesis plane perpendicular to the detector and observe that objects are blurred and slightly tilted toward the center of the xray source path.…”
Section: Discussionmentioning
confidence: 89%
“…Other researchers report 3D performance measures for tomosynthesis (Hu and Zhao, 2011; Gang et al, 2011). We have performed human observer studies to investigate whether readers’ performance increases when the entire volume is shown, rather than the 2D image only, but so far we failed to find clear evidence that human observers can retrieve additional information from the volume, for the task of detecting exactly known signals in a 50°-scan tomosynthesis system (Reiser and Nishikawa, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…The DBT volume has unique properties compared to CT, namely the depth resolution in DBT is non-isotropic and depends on the DBT system scan range as well as the extent of the object in the direction of the X-ray tube scan 26 . Our preliminary studies have indicated that human reader performance does not improve when information on adjacent is provided 27 , 28 …”
Section: Introductionmentioning
confidence: 89%
“…26 Our preliminary studies have indicated that human reader performance does not improve when information on adjacent is provided. 27,28 Hence, in this work, we further explore the question of whether human readers are able to integrate information from adjacent planes in a 3D lesion detection task, for breast imaging both with DBT and bCT. Images for the reader studies were generated using a directional power-law model with embedded spherical and cylindrical targets and "imaged" with both DBT (50 deg scan angle) and bCT (180 deg scan angle).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation